2014
DOI: 10.2500/ajra.2014.28.4098
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Apparent Diffusion Coefficient in Characterization of Different Sinonasal Pathologies

Abstract: DW-MRI did not add significantly to the information gained from conventional MRI. It should be considered complimentary only to standard MRI in uncertain cases when malignancy is still a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Studies considering DWI in paranasal sinus diseases available in literature focused essentially on ADC comparisons between groups of malignant neoplasms and benign lesions, considering a wide variety of inflammatory lesions in the group of benign lesions [ 20 , 21 , 31-37 ]. Inflammatory diseases exclusively were investigated by two studies [ 22 , 38 ] with distinct objectives and methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies considering DWI in paranasal sinus diseases available in literature focused essentially on ADC comparisons between groups of malignant neoplasms and benign lesions, considering a wide variety of inflammatory lesions in the group of benign lesions [ 20 , 21 , 31-37 ]. Inflammatory diseases exclusively were investigated by two studies [ 22 , 38 ] with distinct objectives and methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MRI is often referred to as the preferable imaging examination in the diagnosis of inflammatory sinus disease [ 18 , 19 ] essentially when further maxillary sinus disease evaluation is needed. Diffusion-weighted MRI (DWI) is a conventional MRI complementary tool that can be employed to the depiction of sinus diseases [ 20-22 ] and analyses qualitatively water molecular random movements in intracellular medium. DWI can be translated into numerical values, named as “apparent diffusion coefficient“ (ADC) which expresses quantitatively water movement.…”
Section: Introductionmentioning
confidence: 99%
“…41 Several studies have shown that ADC mapping can be used to differentiate benign and inflammatory sinus disease from malignant tumors. [42][43][44] Multiparametric MRI using both ADC mapping and dynamic contrast-enhanced MR time-intensity curve analysis has also been shown to have some utility in differentiating between benign and malignant sinonasal lesions. 43 The most common sinonasal neoplasm is squamous cell carcinoma, accounting for approximately 80% of sinonasal cancers.…”
Section: Sinonasal Tumorsmentioning
confidence: 98%
“…DWI and ADC are highly variable. When viscous protein-rich secretions are present, it may have very low ADC values (< 0.5 × 10 −3 mm 2 /s) [ 48 ].
Fig.
…”
Section: Inflammatory Lesions (Table 1 )mentioning
confidence: 99%